1970
DOI: 10.1037/h0082834
|View full text |Cite
|
Sign up to set email alerts
|

Verbal-discrimination learning following a free-recall familiarization training procedure.

Abstract: The effects of transfer from a modified free-recall task to verbal-discrimination (VD) learning were investigated. The free-recall procedure was designed to impart increments in experimental frequency to specific words that appeared in VD. Four experimental groups were given prior free-recall exposure to either all right VD items (A-H), all wrong (A-w), both the right and wrong items from same VD pairs (B-S), or both die right and wrong items from different VD pairs (B-D). A fifth group served as a control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1971
1971
1974
1974

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Consistent with the findings of Berkowitz (1968) and Wallace and Nappe (1970), the prediction from frequency theory that familiarization will slow VD learning received support. Such detrimental effects were much less apparent for VD lists of words of very low language frequency than for lists of common words.…”
Section: Vd Acquisitionsupporting
confidence: 65%
See 1 more Smart Citation
“…Consistent with the findings of Berkowitz (1968) and Wallace and Nappe (1970), the prediction from frequency theory that familiarization will slow VD learning received support. Such detrimental effects were much less apparent for VD lists of words of very low language frequency than for lists of common words.…”
Section: Vd Acquisitionsupporting
confidence: 65%
“…Given some existing frequencies at the outset, a greater number of VD trials are required to reach this ratio. This notion, resembling a Weber's constant, has been supported in some studies (e.g., Berkowitz, 1968;Wallace & Nappe, 1970) but not in others (e.g., Runquist & Freeman, 1960). Lovelace (1969) reported significantly better performance on a VD list of words of very low language frequency when three familiarization trials were given on each word prior to VD learning than when irrelevant familiarization on digits preceded the VD task.…”
Section: In the Verbal-discbimination (Vd) Task Each Subject Is Prese...mentioning
confidence: 94%
“…Further support for frequency theory has come from studies in which transfer paradigms were used (Raskin, Boice, Rubel, & Clark, 1968;Smith & Jensen, 1971;Underwood, Jesse, & Ekstrand, 1964;Wallace & Nappe, 1970). Underwood et al changed either the correct or incorrect words from VD List 1 to List 2, while Raskin et al changed or maintained the correct and incorrect designation of words in two successive lists.…”
mentioning
confidence: 99%
“…The second major point emphasized here is that when all pairs in a list are not uniform with regard to the "rule" that correct alternatives surpass their respective incorrect alternatives in frequency value, VD learning is difficult. It has been demonstrated that VD lists structured to approximate this condition are, indeed, very difficult (Ekstrand et al, 1966;Wallace & Nappe, 1970).…”
mentioning
confidence: 99%